Topical Corticosteroid Pretreatment Mitigates Cellular Damage After Caustic Injury to the Nasal Upper Airway Epithelium. Issue 3 (May 2019) - Huang, Zhenxiao; Velasquez, Nathalia; Nguyen, Alan; Ye, Ting; Le, Wei; Bravo, Dawn T.; Hwang, Peter H.; Zhou, Bing; Nayak, Jayakar V.
Background: Topical corticosteroids are currently employed to reduce established airway inflammation; their prophylactic use might help limit cellular damage against harmful stimuli. Objectives: To determine the effects of a prophylactic topical application of budesonide (BD) on an in vivo nasal epithelium injury model induced by trichloroacetic acid (TCA). Methods: C57Bl/6 mice were exposed to intranasal TCA topical application. Three groups received topical intranasal BD, saline solution, or no intervention prior to a single topical exposure to TCA. Controls were not exposed to TCA. Whole nasal cavity coronal sections were analyzed at 1, 3, and 6 days postinjury at tissue and cellular levels using histopathological analysis, immunofluorescent staining, and fresh tissue RNA microarray analysis. Results: Prophylactic topical corticosteroid exposure protected the nasal epithelium from acute damage, maintaining epithelial thickness and cell survival. Six days following TCA exposure, epithelial and cellular changes were less pronounced on the BD-treated group compared to all exposure groups. The microarray analysis was used to evaluate the gene transcripts in all treatment groups. Ciliary tip protein, Sentan, and submucosal protein S100b were identified as potential factors in epithelial airway protection; immunofluorescent staining corroborated their presence and location within the respiratory epithelium. Conclusion: Topical corticosteroid treatment to the nasal epithelium can mitigate several of the early deleterious effects of acute epithelial damage in experimental airway injuries caused by TCA. These findings suggest a novel, direct cytoprotective effect of corticosteroids on the nasal epithelium, and the potential of expanding the use of prophylactic periprocedural topical corticosteroids for respiratory epithelial tissues.